Effect of Orthodontic Treatment on Tooth Autotransplantation: Systematic Review of Controlled Clinical Trials - Lacerda-Santos, Rogério; Canutto, Rhaíssa Ferreira; Araújo, José Lucas dos Santos; Carvalho, Fabiola Galbiatti de; Münchow, Eliseu Aldrighi; Barbosa, Taís de Souza; Pithon, Matheus Melo; Rego, Emanuel Braga; Neves, Leniana Santos (European Journal of Dentistry, 2020)
This systematic review was focused on evaluating tooth autotransplantation, considering its impacts on the teeth, bone, soft tissues, and aesthetics in orthodontic patients. A bibliographic search was conducted without limitations on year of publication or language in the databases of PubMed, Web of Science, Scopus, Medline Complete, Cochrane, Clinical Trials, and Trials Central. For triage of articles, indications, surgical planning, orthodontic movement, risk factors for treatment, and long-term follow-ups were considered. For outcomes, the results with reference to teeth, alveolar bone, periodontal tissues, and esthetic satisfaction were considered. Risk of bias was evaluated using the methodological index for nonrandomized studies-MINORS. The results showed 10 controlled clinical trials, and no randomized clinical trials were found. The selected studies included 715 patients and 934 autotransplanted teeth among which there were premolars, molars, and anterior teeth evaluated in the long term, indicating that orthodontics associated with autotransplantation indicated a result that was generally clinically acceptable. The quality of the set of evidence was considered medium due to the presence of different methodological problems, risk of bias, and significant heterogeneity in the evaluated studies. There was a sufficient body of evidence that justified autotransplantation in patients who needed orthodontic movement. In teeth, there was an increase in root resorption influenced by orthodontics, but without impacting on the general clinical result in the long term. Bone and periodontal tissue do not appear to be affected by orthodontics. The patient’s aesthetic satisfaction was not considered in the studies.
Keywords: transplantation; success rate; root resorption; survival rate; orthodontics